APLIKASI TEKNOLOGI SISTEM INFORMASI GEOGRAFIS DAN PENGINDERAAN JAUH UNTUK PENENTUAN KONDISI DAN POTENSI KONSERVASI EKOSISTEM HUTAN MANGROVE DI KECAMATAN KWANYAR KABUPATEN BANGKALAN - Wahyu A'idin Hidayat; Zainul Hidayah; Wahyu Andy Nugraha (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2011)
Given the importance of mangrove ecosystems in supporting the preservation of coastal resources, as well as threats to the sustainablity, a research to determine current conditions and potential for conservation of mangrove ecosystem in the coastal District Kwanyar Regency Bangkalan is needed. This research combines on site observation techniques, Geographical Information System (GIS) and remote sensing to obtain accurate and the latest data. Furthermore, the data is possible to be updated. Objectives of this research are to examine the distribution of mangrove vegetations in Kwanyar District using GIS, to analyze the condition of the mangrove ecosystem based on RBI Map, Landsat Imagery, and field conditions and also to determine the areas that have potential condition as a mangrove conservation area. Methods of this research are adopted from the Ministry of Forestry in 2006. Results of this research showed that based on the RBI Map scale 1: 25.000 from 2006, Landsat imagery from 2002 and field survey on 2008, that are processed by Geographical Information System (GIS), the result showed that area covered by mangrove ecosystem in Kwanyar District are 140.76 ha and have been damaged. The data obtained from the results of scoring according to the rules issued by the Ministry of Forestry in 2006 showed that there was no area in the location that can be recommended as a conservation area. However, it can be argued that the village of Pesanggrahan has the better condition of mangrove ecosystems, therefore it has potency to be developed as a conservation area in the future. Keywords: Geographical Information System, Remote Sensing, Conservation, Mangroves